Identifying Patients at Risk for Prehospital Sudden Cardiac Arrest at the Early Phase of Myocardial Infarction: The e-MUST Study (Evaluation en Médecine d'Urgence des Stratégies Thérapeutiques des infarctus du myocarde). Issue 25 (20th December 2016) - Karam, Nicole; Bataille, Sophie; Marijon, Eloi; Giovannetti, Olivier; Tafflet, Muriel; Savary, Dominique; Benamer, Hakim; Caussin, Christophe; Garot, Philippe; Juliard, Jean-Michel; Pires, Virginie; Boche, Thévy; et al.
Abstract : Background: In-hospital mortality of ST-segment–elevation myocardial infarction (STEMI) has decreased drastically. In contrast, prehospital mortality from sudden cardiac arrest (SCA) remains high and difficult to reduce. Identification of the patients with STEMI at higher risk for prehospital SCA could facilitate rapid triage and intervention in the field. Methods: Using a prospective, population-based study evaluating all patients with STEMI managed by emergency medical services in the greater Paris area (11.7 million inhabitants) between 2006 and 2010, we identified characteristics associated with an increased risk of prehospital SCA and used these variables to build an SCA prediction score, which we validated internally and externally. Results: In the overall STEMI population (n=8112; median age, 60 years; 78% male), SCA occurred in 452 patients (5.6%). In multivariate analysis, younger age, absence of obesity, absence of diabetes mellitus, shortness of breath, and a short delay between pain onset and call to emergency medical services were the main predictors of SCA. A score built from these variables predicted SCA, with the risk increasing 2-fold in patients with a score between 10 and 19, 4-fold in those with a score between 20 and 29, and >18-fold in patients with a score ≥30 compared with those with scores <10. The SCA rate was 28.9% in patients with a score ≥30 compared with 1.6% in patients with a score ⩽9 ( P for trend <0.001). The area under the curve values were 0.7033 in the internal validation sample and 0.6031 in the external validation sample. Sensitivity and specificity varied between 96.9% and 10.5% for scores ≥10 and between 18.0% and 97.6% for scores ≥30, with scores between 20 and 29 achieving the best sensitivity and specificity (65.4% and 62.6%, respectively). Conclusions: At the early phase of STEMI, the risk of prehospital SCA can be determined through a simple score of 5 routinely assessed predictors. This score might help optimize the dispatching and management of patients with STEMI by emergency medical services. Abstract : Supplemental Digital Content is available in the text.